Social Media for Social Support: A Study of International Graduate Students in the United States - Baines, Annalise; Ittefaq, Muhammad; Abwao, Mauryne (Journal of International Students, 2021)
Based on 15 in-depth interviews, the present study aims to understand the common challenges international graduate students face and the coping strategies they employed, types of social networking sites (SNS) used, and social support sought from their relationship during graduate school. Common challenges faced are loneliness, stress, feeling overwhelmed with graduate school, and difficulties adjusting to a new culture. Coping strategies include sharing experiences with relations whom they trust and understand their situation, and joining online communities via SNS. The participants use both public and private SNS to seek social support depending on the various functionalities offered. SNS use depends on the affordances such as convenience, affordability, trust issues, and privacy. Most sought-after types of social support are emotional and informational via SNS.